Software Requirement Specification Sistem Informasi Manajemen Rumah Makan Berdasarkan ISO/IEC/IEEE 29148-2018 - Dwi Januarita; Wahyu Adi Prabowo (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
The rapid development of technology makes this technology have an impact on many fields, one of which is the business world. The number of businesses that have emerged both small and large businesses that have an impact on competition between these businesses. Today, business in the culinary field is getting tougher. The culinary business sector of restaurants is increasingly popping up in this age. We need to overcome the competition in the emerging restaurant business. By using the stages of making software requirements specifications based on ISO / IEC / IEEE 29148-2018, this restaurant business will have an international standard information system. The result of this method is a software requirements specification document (SKPL) as a reference document for all activities carried out during the development of this information system.